Dietary fish oil replacement with lard and soybean oil affects triacylglycerol and phospholipid muscle and liver docosahexaenoic acid content but not in the brain and eyes of surubim juveniles Pseudoplatystoma sp - Noffs, M. D.; Martino, R. C.; Trugo, L. C.; Urbinati, Elisabeth Criscuolo [UNESP]; Fernandes, J. B K [UNESP]; Takahashi, L. S. [UNESP] (Springer Nature, 2009)
Triplicate groups of juvenile suribim were fed for 183 days one of four different isonitrogenous (47.6% crude protein) and isolipidic (18.7% lipid) diets formulated using three different lipid sources: 100% fish oil (FO, diet 1); 100% pig lard (L, diet 2); 100% soybean oil (SO, diet 3), and FO/L/SO (1:1:1, w/w/w; diet 4). The tissue levels of fatty acids 18:2n - 6 and 18:3n - 3 decreased relative to corresponding dietary fatty acid values. The 20:5n - 3 and 22:6n - 3 composition of muscle and liver neutral lipids were linearly correlated with corresponding dietary fatty acid composition. In contrast, the 22:6n - 3 composition of the brain and eye were similar among treatments. The 22:6n - 3 level was enriched in all tissues, particularly in the neural tissues. Similar results were observed for tissue polar lipids: fatty acids content reflected dietary composition, with the exception of the 22:6n - 3 level, which showed enrichment and no differences between groups. Given these results, the importance of the biochemical functions (transport and/or metabolism) of 22:6n - 3 in the development of the neural system of surubim warrants further investigation. © Springer Science+Business Media B.V. 2008.
Keywords: Fish oil; Lipid metabolism; Phospholipids; Pig lard; Polyunsaturated fatty acids; Pseudoplatystoma sp.; Soybean oil; Triacylglycerols; docosahexaenoic acid; fish oil; lard; soybean oil; analysis of variance; animal; aquaculture; brain; catfish; comparative study; eye; fat intake; gas chromatography; liver; metabolism; skeletal muscle; Analysis of Variance; Animals; Aquaculture; Brain; Catfishes; Chromatography, Gas; Dietary Fats; Docosahexaenoic Acids; Eye; Fish Oils; Liver; Muscle, Skeletal; Soybean Oil; Glycine max; Pseudoplatystoma; Suidae